2012
DOI: 10.1002/ajim.22026
|View full text |Cite
|
Sign up to set email alerts
|

Injuries caused by work‐related violence: Frequency, need for medical treatment and associations with adverse mental health and alcohol use among Finnish police officers

Abstract: Among police officers, high frequency and the need for medical treatment of injuries is associated with an increased risk of adverse mental health. High frequency of injuries may also increase alcohol consumption among police officers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…The Finnish study also found that officers who experienced more than one injury arising out of work-related violence were significantly more likely to report increased alcohol consumption, psychological distress symptoms, and fear of future violence. Further, among officers who had suffered injuries, the need for medical attention when injured was associated with increased odds of each of the aforementioned outcomes (Leino et al 2012). Findings such as these highlight the imperative to identify and manage ways of working that might be associated with elevated risk of violent victimisation.…”
Section: Implications Of Police Officer Violent Victimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Finnish study also found that officers who experienced more than one injury arising out of work-related violence were significantly more likely to report increased alcohol consumption, psychological distress symptoms, and fear of future violence. Further, among officers who had suffered injuries, the need for medical attention when injured was associated with increased odds of each of the aforementioned outcomes (Leino et al 2012). Findings such as these highlight the imperative to identify and manage ways of working that might be associated with elevated risk of violent victimisation.…”
Section: Implications Of Police Officer Violent Victimisationmentioning
confidence: 99%
“…Responses were dichotomised into (i) zero and (ii) once or more. The focus on more serious injuries that required medical attention was informed by Finnish police research demonstrating that officers who required medical attention due to injuries arising from work-related violence were 2.33 times more likely to display psychological distress symptoms, 2.08 times more likely to report increased risk for increased alcohol consumption, and 2.09 times more likely to report fear of future violence relative to those who had no need for medical attention after suffering such an injury (Leino et al 2012).…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…[5] Frequent sustaining of injuries and the need for medical treatment is associated with an increased risk of adverse mental health. [6] Police officers who suffered more than one injury had a relative risk of 4.9 for increased alcohol consumption and 4.4 relative risk for psychological distress symptoms compared to those who suffered no injuries. [6] Injuries especially musculoskeletal may decrease the involvement of police officers in physical exercises.…”
Section: Introductionmentioning
confidence: 94%
“…[6] Police officers who suffered more than one injury had a relative risk of 4.9 for increased alcohol consumption and 4.4 relative risk for psychological distress symptoms compared to those who suffered no injuries. [6] Injuries especially musculoskeletal may decrease the involvement of police officers in physical exercises. Post trauma stress (PTSD) may also be an important factor responsible for the development of this attitude.…”
Section: Introductionmentioning
confidence: 94%
“…Police who are exposed to violence are exposed to a greater risk of depressive symptoms (36) and psychological distress (37). In a Swedish study a significant association was identified between the rate of sickness absence from work and police who were exposed to threats of violence, discrimination or sexual harassment in the workplace (38).…”
Section: Introductionmentioning
confidence: 99%